Alterations of oral microbiota in patients with panic disorder. Issue 1 (1st January 2021) - Xie, Zunli; Jiang, Weiqing; Deng, Mingzhu; Wang, Wei; Xie, Xian; Feng, Xia; Shi, Yinping; Zhang, Xueyan; Song, Dong; Yuan, Ziyu; Wang, Yonggang
ABSTRACT: The main characteristics of panic disorder (PD) include recurrent panic attacks and persistent worry, accompanied by other physical and cognitive symptoms. While recent studies have revealed that gut bacteria play an important role in anxiety and depression, little is known about the relationship between oral microbiota and PD. Therefore, the objective of this study was to explore a possible correlation between oral microbiota and PD. We conducted 16S rRNA sequencing to compare differences in the oral microbiota of patients with PD (n = 26) and healthy controls (n = 40). Patients with PD exhibited higher alpha diversity (abundance and evenness) in their oral microbiota than healthy controls, while analysis of beta diversity revealed that the two groups differed in microbial community composition. Moreover, the relative abundance of 61 genera differed between them. Overall, PD resulted in distinct oral microbial profiles that could be potential diagnostic markers and therapeutic targets.